Health risks for body pierced community: a systematic review. (April 2022) - Sindoni, A.; Valeriani, F.; Protano, C.; Liguori, G.; Romano Spica, V.; Vitali, M.; Gallè, F.
Abstract: Objective: Body piercing is defined as the penetration of jewellery into openings made in different body areas. In the last decades, it has become increasingly common in the general population. The aim is to analyse the available literature about complications from body piercing for contributing to raise the awareness towards this issue and to plan and perform appropriate prevention interventions. Study design: This is a systematic review. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used to perform this systematic review; the protocol was registered with PROSPERO [CRD42020177972]. PubMed, Scopus and Web of Science were searched from database inception to April 2020, and articles in English language reporting a proven association between piercings and health risks were included, and their quality were assessed by adequate quality assessment tools. Results: A total of 4748 studies were found, and after duplicates removal and screening, 84 articles were included. Studies dealing with microbiological effects reported these complications both locally and at distant sites as a result of the spreading of the primary site infection: mastitis, endocarditis, glomerulonephritis, cephalic tetanus, viral hepatitis, HIV, cerebellar brain abscess and toxic shock syndrome. In addition, bleeding, gingival recession, dental injuries, contact dermatitis, granulomatous dermatitis, keloid, fibroma and basal cell carcinoma were reported. Conclusions: Health authorities should promote educational campaigns to spread the knowledge on health risks related to piercings. Besides, piercers are often not adequately aware of all the possible adverse effects due to piercings because their professional training differs among countries. It is therefore advisable to provide periodical upgrade of their education in this field.